Clinico-pathologic profile of skin cancers in oculocutaneous albinism at Universitas Academic Hospital - Molikuoa Harriet Makuru; Frans Maruma; Edward Ngwenya; Kelvin Mponda (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Oculocutaneous albinism (OCA) is a genetic disorder found worldwide. Skin cancer is a significant risk for people with albinism, particularly in Africa, where it is a major cause of death. Many patients delay seeking medical care until their skin lesions are in advanced stages.